Arterial hypertension as a consequence of endothelial glycocalyx dysfunction: a modern view of the problem of cardiovascular diseases - M. M. Ziganshina; A. R. Ziganshin; E. O. Khalturina; I. I. Baranov (Кардиоваскулярная терапия и профилактика, 2022)
Arterial hypertension (AH) is a leading risk factor for the development of cardiovascular, cerebrovascular, and renal diseases, which are among the top 10 most common causes of death in the world. The etiology of hypertension has not been fully elucidated, but it has been established that endothelial dysfunction is the most significant pathogenetic link in the formation and progression of the disease. The data obtained in the last 10-15 years on endothelial glycocalyx (eGC) studies indicate that endothelial dysfunction is preceded by destabilization and shedding of eGC with the appearance of its soluble components in the blood, which is equivalent to a process that can be designated as eGC dysfunction. Signs of eGC dysfunction are expressed in the development of hypertension, diseases of the cardiovascular system, and their complications. The purpose of this review is to analyze and substantiate the pathophysiological role of eGC dysfunction in hypertension and cardiovascular diseases and to describe approaches for its assessment and pharmacological correction. Abstracts and full-size articles of 425 publications in Pubmed/MEDLINE databases over 20 years were studied. The review discusses the role of eGC in the regulation of vascular tone, endothelial barrier function, and anti-adhesive properties of eGC. Modifications of eGC under the influence of pro-inflammatory stimuli, changes in eGC with age, and with increased salt load are considered. The aspect associated with eGC dysfunction in atherosclerosis, hyperglycemia and hypertension is covered. Assessment of eGC dysfunction is difficult but can be performed by indirect methods, in particular by detecting eGC components in blood. A brief description of the main approaches to pharmacoprevention and pharmacocorrection of hypertension is given from the position of exposure effects on eGC, which currently has more a fundamental than practical orientation. This opens up great opportunities for clinical studies of eGC dysfunction for the prevention and treatment of hypertension and justifies a new direction in the clinical pharmacology of antihypertensive drugs.